The singing songs role in teaching "My Arabic language subject" from the point of view of Educational mentors and teachers at the first Colloquium of the Basic education (Actual Field Study at Lattakia City) - Jnad, Roua; Ker Beek, Hend; Ibrahim, Ramadan (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aimed to Specifying the role of singing songs in teaching of Arabic subject from the point of view of Educational mentors and teachers at the first Colloquium of the Basic Education at Lattakia City. The researcher followed the descriptive method, The research tool consisted of a questionnaire in which the researcher examined the views of the Educational mentors of the first Colloquium and their teachers from the basic education stage in Lattakia about the role of singing songs in the teaching of my language Arabic subject . The sample included (18) Educational mentors and (160) teachers and( 12.27 %) Of the original community of teachers in Lattakia, were chosen randomly, and the research tool was presented to a group of arbitrators and verified its validity and consistency, and then applied in the academic year 2016-2017. The research showed the following results and the most important were: There are no statistically significant differences at the level of significance(0.05) between the averages of the degrees (mentors and the teachers) in their opinions about the role of singing songs in teaching of my Language Arabic subject according to the variables (gender and educational experience); and this is due to their awareness of the importance of the singing songs in teaching my Language Arabic as an interesting useful scientific method of shortening time and effort, whereas There are statistically significant differences at the averages of the degrees of the Educational mentors and the teachers in their opinions of the role of singing songs in teaching of my Language Arabic according to the variables (type of work and scientific qualification ) for the benefit of mentors and high educational specialists . In the light of the results The research suggested : 1 - The need to prepare qualified academic and educational teachers to teach the songs in the halls of the availability of suitable educational means, after the introduction to the curriculum or composed by them, the research confirmed that it is still absent from the ground until the moment of doing this research. 2 - Adoption of the criteria reached in the selection of songs.